Interior Batik Gallery Using Normal Mapping For Virtual Reality - Padmasari, Ayung Candra; Christyowidiasmoro, Christyowidiasmoro; Hariadi, Mochamad (IPTEK Journal of Proceedings Series, 2014)
We present an 3D Modelling  object for  batik Gallery  in virtual reality with textured material photo,  Lighting effect  and primitive mess with Normal Mapping Metthod. Normal Mapping is one of many method  to  give  depht  Impression texture and detail for object without  many   polycount, so we can get  efficiency of the computer work without loss of detail desired.  in this research  we try to explain  several techniques in making batik Gallery design textures with  modeling 3D,  The methods include stage Normal Mapping, Environment maps, bump maps, and shadow maps. The next proscess we can use Directional Light and Point Light for each object to get the  impression of depth and real dimension for each  texture.  The result of this research is  to improve  the modern batik consept and patterns with immersive  3D Room  in Virtual reality